1985
DOI: 10.1007/bf02265403
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamically significant PDA: An echocardiographic and clinical assessment of incidence, natural history, and outcome in very low birth weight infants maintained in negative fluid balance

Abstract: Fifty very low birth weight (VLBW) infants (750-1500 g, 27-33 weeks gestational age) were assigned at random to one of two groups of negative fluid balance and underwent prospective clinical and echocardiographic examinations during the first month of life. The purpose was to determine: the effect of fluid restriction on the incidence of ductal shunting, the reliability of the physical examination in diagnosing significant ductal shunting, and the relationship between significant ductal shunting and outcome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Reller et al [13] also found that in VLBW infants, birth asphyxia and severe RDS were significant risk factors for development of an early hemodynamically significant PDA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Reller et al [13] also found that in VLBW infants, birth asphyxia and severe RDS were significant risk factors for development of an early hemodynamically significant PDA.…”
Section: Discussionmentioning
confidence: 95%
“…Besides immaturity and severity of illness frequently presented by preterm infants, other parameters, namely, the Apgar score, presence of metabolic acidosis and need for supplemental oxygen are also considered when scoring [14], all contributing to PDA, as noted above [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, oxygen saturations in the range of 83 to 89% do not appear to impact the response of the DA to pharmacological closure as the rate of surgical ligation remained unchanged. Several factors affect the incidence of PDA in preterm neonates including GA, 1 intrauterine growth restriction, 18 antenatal steroids, 19,20 low Apgar scores 21 and the presence of respiratory distress syndrome. 22 When adjusted for these factors using univariate and multivariate logistic regression, the odds of having an hsPDA remained higher with the low oxygen saturation limits.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In these neonates, the incidence of a persistent patent DA (PDA) increases with decreasing estimated gestational age (EGA) and BW, [2][3][4][5] although not all studies have arrived at this conclusion. 6 As a group, as many as 31% of very low BW neonates develop a clinically and hemodynamically significant PDA (sPDA) with signs of increased left to right shunting, pulmonary edema and an enlarged cardiothymic shadow on chest X-ray. 7 The presence of a sPDA in very low BW preterm neonates has been associated with pulmonary edema and hemorrhage, prolonged mechanical ventilation and oxygen requirement, development of bronchopulmonary dysplasia (BPD) or chronic lung disease, necrotizing enterocolitis, intracranial hemorrhage and retinopathy of prematurity.…”
Section: Introductionmentioning
confidence: 99%